1998
DOI: 10.1093/rheumatology/37.9.952
|View full text |Cite
|
Sign up to set email alerts
|

Oral iloprost in Raynaud's phenomenon secondary to systemic sclerosis: a multicentre, placebo-controlled, dose-comparison study

Abstract: The results on the daily duration of Raynaud's attacks suggest that both 50 and 100 microg oral iloprost twice daily may be effective in the treatment of Raynaud's phenomenon secondary to systemic sclerosis. The 50 microg iloprost dose was better tolerated in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 1 publication
3
56
1
5
Order By: Relevance
“…However, reported placebo responses for clinical outcome variables in other RP studies is usually Ͻ20% from baseline (20), which is substantially less than the 49% reduction in severity and 50% reduction in frequency of RP episodes observed for losartan in the present study. That the clinical benefit of losartan was less evident in scleroderma patients is in keeping with the results from other studies which have suggested that treatment with vasodilators is less effective for secondary RP (8,21,22).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…However, reported placebo responses for clinical outcome variables in other RP studies is usually Ͻ20% from baseline (20), which is substantially less than the 49% reduction in severity and 50% reduction in frequency of RP episodes observed for losartan in the present study. That the clinical benefit of losartan was less evident in scleroderma patients is in keeping with the results from other studies which have suggested that treatment with vasodilators is less effective for secondary RP (8,21,22).…”
Section: Discussioncontrasting
confidence: 80%
“…Although subjective, self-reporting of RP symptoms appears to be a reliable assessment tool, particularly when combined with longitudinal analysis of the data (20). The results for serum markers provide additional indirect evidence that losartan could benefit the underlying pathologic processes in individuals with secondary RP.…”
Section: Discussionmentioning
confidence: 94%
“…A dose-dependent improvement of skin microcirculation and of transcutaneous oxygen tension is observed in the affected ischemic extremity [19, 20]. Iloprost is also the treatment of choice for digital necrosis associated with systemic sclerosis [21, 22, 23]. Our observation supports the hypothesis that Raynaud’s phenomenon and digital necrosis due to thromboangiitis obliterans can be cured by this drug.…”
Section: Discussionsupporting
confidence: 81%
“…Randomized controlled trials evaluating use of intravenous iloprost for PAH have not been conducted (Provencher and Sitbon, 2009). An oral iloprost preparation has been used in investigational studies of Raynaud's phenomenon secondary to systemic sclerosis (Black et al, 1998); its value in PAH is not known.…”
Section: Clinical Studies (Inhalation)mentioning
confidence: 99%